Molecular dynamics and finite elements: an approach to couple different worlds. Issue 1 (December 2014) - Pfaller, Sebastian; Possart, Gunnar; Steinmann, Paul
Abstract The procedure proposed here couples a continuum with a particle region by introducing an overlapping bridging domain where both regions exchange information. Beyond existing methods, the particle region is computed by Molecular Dynamics (MD) at finite temperature, using a code that has been developed by our co‐workers of the Theoretical Physical Chemistry Group at TU Darmstadt. It is also used in the wide field of physical chemistry for various approaches. In contrast to MD procedures employing periodic boundary conditions (PBC), stochastic boundary conditions (SBC) allow for the definition of static anchor points. These additional artificial particles are coupled to the continuum part and serve as information transmitter. The continuum is treated classically by the Finite Element Method (FEM) which has been adapted based on the Arlequin and the bridging domain method. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)